The complete mitochondrial genome of the Madagascar banded commodore butterfly Precis andremiaja (Insecta: Lepidoptera: Nymphalidae) - Melanie M. L. Lalonde; Jeffrey M. Marcus (Mitochondrial DNA. Part B. Resources, 2019)
The endemic Madagascar banded commodore butterfly Precis andremiaja Boisduval, 1833 (Nymphalidae) inhabits forest margins and disturbed habitats. Genome skimming by Illumina sequencing allowed the assembly of a complete circular mitogenome of 15,239 bp from P. andremiaja consisting of 80.2% AT nucleotides, 22 tRNAs, 13 protein-coding genes, 2 rRNAs and a control region in the typical butterfly gene order. Precis andremiaja COX1 has a CGA start codon and COX1, COXII, NAD4 and NAD5 exhibit incomplete stop codons. Phylogenetic reconstruction places P. andremiaja as sister to Hypolimnas bolina within a monophyletic nymphalid tribe Junoniini, which is consistent with previous molecular phylogenetic hypotheses.